Oral Health-Related Quality of Life among Children and Adolescents with Autism Spectrum Disorder: A Cross-Sectional Study - Stephanie Vieira de Souza; Michelle Estefane da Silva Damasceno; Rachid Pinto Zacarias Filho; Simone Assayag Hanan (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the oral health-related quality of life (OHRQoL) of children and adolescents with autism spectrum disorder (ASD) through parental/caregiver perceptions. Material and Methods: Children and adolescents aged 4-18 years enrolled in an ASD center at Manaus, AM, Brazil, were assessed for dental caries by clinical examination. A trained and calibrated examiner performed all exams. The "Parental-Caregiver Perceptions Questionnaire" (PCP-Q) and the "Family Impact Scale" (FIS) were used to assess OHRQoL. Data analysis was performed using descriptive statistics and the Mann-Whitney U test. Results: Fifty-one children/adolescents of both sexes participated in the study. The mean age of patients was ten years (3.0), and most were male (76.5%). Forty-five (88.2%) mothers had more than nine years of schooling, and 28 (54.9%) earned equal to or less than two Brazilian minimum wages. The global PCP-Q score ranged from 0 to 25, with a mean value of 7.41 (6.64). The impact score values were significantly higher in individuals with caries experience in primary dentition (p<0.05). No significant differences in OHRQoL scores existed regarding family income and maternal schooling. Conclusion: According to parental/caregiver perceptions, children and adolescents with ASD had a higher impact on the PCP-Q functional limitation domain. Caries experience in primary teeth contributed to higher mean scores in all PCP-Q domains.